Impact of the Skill Shortage on the Construction Supply Chain Performance in Australia - Ming Juan Ding; Ferry Jie; Sommala Sisombat; Bala S. Bandlamudi (Salehan Institute of Higher Education, 2023)
The purpose of this paper is to investigate how the skill shortage impacts the performance of the construction supply chain in Australia. The study has adopted a quantitative research method. The quantitative data were collected by conducting a survey of employees who work in construction companies in Australia. A regression analysis was used to analyze the data from 113 respondents. The findings of the study reveal that the construction sector in Australia has high labour costs, but workers are still thinking they are not getting paid enough and cannot invest more in themselves to improve their skills. There is a lack of academic and vocational training programs offered to them. Insufficient recruitment and incentive policies are also main barriers to attract talents to the construction industry in Australia. The situation became more serious during the COVID-19 period due to the lockdowns, lack of skilled migrants, and Government working visa policies. The study implies that firms should have a deeper understanding of the reasons for the skill shortage. Firms also need to devise strategies for hiring the right talent. Further, it was found that quality talent can come from the local or foreign markets. More effective selection criteria should be designed so that the best-fit approach can be implemented. Doi: 10.28991/CEJ-2023-09-02-08 Full Text: PDF